Probabilistic algorithms for power load flow and short-circuit analysis in distribution networks with dispersed generation - Peñuela Meneses, César Augusto [UNESP]; Echeverri, Mauricio Granada; Sanches Mantovani, Jose R. [UNESP] (Springer Nature, 2013)
In this paper, an approach for probabilistic analysis of unbalanced three-phase weakly meshed distribution systems with dispersed generation is presented. The approach considers uncertainty in both load demand and the injected power of dispersed generators. In order to achieve high computational efficiency, the approach makes use of both an efficient method for probabilistic analysis and a radial power flow. The probabilistic strategy used is the well-known Three-Point Estimate Method. In the other hand, classical models based on the sequence impedance are implemented for modeling synchronous machines, asynchronous machines, and electronically interfaced sources. These models aim to consider the impact on the power flows from the installation of dispersed generators. A small-size test system, as well as the modified IEEE 123 bus system, is used to show the operation and effectiveness of the proposed approach. A Monte Carlo Simulations method is used to validate the results. © 2013 Brazilian Society for Automatics - SBA.
Keywords: Distributed generation; Distribution power flow; Point Estimate Method; Probabilistic analysis; Short-circuit analysis